The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2004
DOI: 10.1590/s0103-97332004000500072
|View full text |Cite
|
Sign up to set email alerts
|

SR-TXRF detection limit reduction using thin polymer film substrates

Abstract: Three different substrates for the analysis of liquid samples by Total Reflection X-Ray Fluorescence with Synchrotron Radiation (SR-TXRF) were investigated and compared: Lucite (Perspex), Kimfoil and Mylar. Dry targets were prepared by pipetting 5 µl aliquotes of the liquid samples (synthetic standards and fresh water samples) on the different substrates. A five fold reduction of the continuous background and a corresponding reduction of the elementary detection limits were observed when thin polymer film subs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 10 publications
0
8
0
1
Order By: Relevance
“…The LOD is correlated with the signal peak and the background for the measurement of fluorescence spectrum. Several calculation methods of the limit of detection in X-ray spectroscopy have been reported in literatures [9][10][11]. The beam current, counting time and accelerating voltage play the key role for calculating the detection limits.…”
Section: Limit Of Detectionmentioning
confidence: 99%
“…The LOD is correlated with the signal peak and the background for the measurement of fluorescence spectrum. Several calculation methods of the limit of detection in X-ray spectroscopy have been reported in literatures [9][10][11]. The beam current, counting time and accelerating voltage play the key role for calculating the detection limits.…”
Section: Limit Of Detectionmentioning
confidence: 99%
“…When the fluorescence spectrum is measured, the MDL is correlated with the signal peak and the background. Different methods have been reported for calculation of the minimum detection of limits in X-ray spectroscopy [9][10][11]. The detection limits are calculated in PIXE analysis by assuming that the minimum intensity of the peak is three times the square root of the background at full width half maximum intensity.…”
Section: Equipment and Measurementsmentioning
confidence: 99%
“…There were, however, a number of crucial flaws in the dried thin method. First of all, Poli et al (2004) reported that as a result of a dissimilarity in the drying process of liquid samples on substrate film, the differences in adhesion and crystallization of the liquid sample may have occurred. Partially evaporation of components during drying process of liquid sample on a film layer can also create an unsound analytical result.…”
Section: Introductionmentioning
confidence: 99%